A176: Deep Sequencing Reveals Differential Small RNA Expression in Serum Exosomes of Children With Juvenile Idiopathic Arthritis. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Jiang, Kaiyu; Hu, Zihua; Chen, Yanmin; Jarvis, James N.
Abstract : Background/Purpose: The number of effective medications for the treatment of JIA has rapidly expanded, and studies have demonstrated that aggressive treatment of early JIA results in improved clinical outcomes. Therefore biomarkers for early diagnosis and prediction of therapeutic outcome are highly desirable. Exosomes, endosome‐derived membrane microvesicles, contain specific RNA transcripts that are thought to be involved in cell‐cell communication. Of these RNA transcripts, microRNAs are the most abundant. These microRNAs have great potential as disease biomarkers. This study was aimed at characterizing exosomal microRNA profiles in children with polyarticular JIA and determining whether such profiles might be disease state‐specific. Methods: Plasma samples were obtained from children with RF‐negative, polyarticular JIA as well as healthy controls (HC; n = 5). Children with JIA had either active, untreated disease (AD, n = 5) or were in clinical remission on medication (CRM; n = 5) as established by the Wallace criteria. Exosomes were isolated from plasma using ExoQuick Precipitation methods. Expression of CD63 (a marker for exosomes) in all samples was validated by western blot. MicroRNA samples were isolated from exosomes using the miRNeasy Micro kit. Small RNA libraries were prepared using standard methods. Sequencing was performed using the Illumina HiSeq 2500 platform. The pass filter reads were mapped to the genome (GRCH37/hg19) using Bowtie 2. Differentially expressed (DE) microRNA were determined using edgeR using a P‐value of 0.05. Results: Plasma exosomal RNAs demonstrated both disease and disease‐state specificity. For example, when we compared AD to HC, there were 30 DE miRNAs (24 down‐regulated, 6 up‐regulated) and 15 small nucleolar RNA (24 down‐regulated, 6 up‐regulated) that demonstrated a 1.6 fold change or greater. We found 11 DE miRNAs (down‐regulated) and 35 DE snoRNA (up‐regulated) that showed a 2.0 fold of greater difference when we compared CRM vs HC. Ingenuity pathway analysis demonstrated that the DE miRNAs are associated with inflammatory disease, connective tissue disorders and skeletal and muscular disorders (e.g. miR‐10, miR‐22, miR‐29, miR‐146, miR‐154, miR‐320, miR‐374 and miR‐500). Four miRNAs (miR‐146a, miR‐146b, miR‐24‐2 and miR‐320b‐2) were common to the AD vs HC and the CRM vs HC comparisons. Further evidence that the plasma exosomal RNA repertoire is disease‐state specific was seen in direct comparison of the AD vs CRM samples. There were 21 DE miRNAs (2 down‐regulated, 19 up‐regulated) and 24 DE snoRNA in the AD vs CRM comparison. These miRNA included let‐7, miR‐21, miR‐143, miR‐148, miR‐154, miR‐379 and miR‐432, which associated with hereditary, skeletal, muscular, and developmental disorders. Conclusion: We demonstrate that the repertoire of small RNA molecules in the plasma of children with JIA differs significantly from those seen in the plasma of healthy children. Furthermore, these RNAs show disease‐state specificity, suggesting that they may be directly involved in therapeutic response. Further characterization of these exosomal miRNAs in JIA may provide greater insight into pathobiology and open new doors for the development of blood‐based biomarkers for JIA.